2003
DOI: 10.1007/s00420-002-0429-y
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of the efficacy of skin barrier creams and protective gloves on percutaneous absorption of industrial solvents

Abstract: Our in vitro experiments could not demonstrate an efficacy of SBC to protect skin penetration for the tested solvents. The percutaneous absorption of all solvents in 50% solution was increased through skin treated with SBCs. Furthermore, SBCs enhance the penetration rates of solvents from complex mixtures compared with the single solvents. The tested gloves showed sufficient protection for the hydrophilic solvents, but not for TMB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 26 publications
1
12
0
4
Order By: Relevance
“…This phenomenon of skin barrier creams, known as ''penetration enhancement'', is well established by experimental data in diffusion cell studies using various industrial chemicals. [33][34][35] In the rubber industry, AA in the workplace air are primarily bound on particles. 36 The use of skin barrier creams with this type of exposure of hazardous substances at workplaces could promote the adherence of particles to the treated skin.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon of skin barrier creams, known as ''penetration enhancement'', is well established by experimental data in diffusion cell studies using various industrial chemicals. [33][34][35] In the rubber industry, AA in the workplace air are primarily bound on particles. 36 The use of skin barrier creams with this type of exposure of hazardous substances at workplaces could promote the adherence of particles to the treated skin.…”
Section: Discussionmentioning
confidence: 99%
“…16 Their use should not be over promoted as this may confer on workers a false sense of security and encourage them to be complacent in implementing the appropriate preventative measures. Despite experimental data showing the efficacy of barrier creams, 17 their potential value is still viewed with scepticism. 18 After-work creams A well conducted trial has shown that moisturisers may increase the susceptibility to irritants, yet in practice 19 afterwork creams appear to confer some degree of protection against developing ICD.…”
Section: Barrier Creamsmentioning
confidence: 99%
“…Skin barrier creams and protective gloves were developed for topical skin protection from exposure to chemical agents [100] and for the reduction of percutaneous absorption of industrial solvents [101] .…”
Section: Penetration Reducersmentioning
confidence: 99%